Long-term motor, functional, and academic outcome following childhood ischemic and hemorrhagic stroke: A large rehabilitation center-based retrospective study. (17th February 2018) - Yvon, Estelle; Lamotte, Delphine; Tiberghien, Anne; Godard, Ingrid; Mardaye, Alain; Laurent-Vannier, Anne; Agostini, Maria De; Chevignard, Mathilde
ABSTRACT: Objective : To study the long-term outcomes following childhood ischemic and hemorrhagic stroke. Methods : This was a retrospective study, looking at children consecutively admitted to a rehabilitation department following childhood stroke. We collected demographic, medical, and severity data, motor deficit, cognitive assessment, and long-term academic outcome. Results : One hundred and twenty-eight children were included, following arterial ischemic (AIS; n = 46) or hemorrhagic (HS; n = 82) stroke. At discharge, motor deficit was still present in 70% of children (versus 89% immediately after stroke). HS predicted significantly better motor and functional outcomes than AIS. After a median follow-up of 43 months, 40% received special education. The receipt of special education was predicted by persistent motor deficit, but when full-scale IQ was taken into account, IQ was the only significant predictor of special education. Conclusions : Childhood stroke leads to severe and long lasting motor, functional, cognitive, and academic impairments, in a population of children admitted in a rehabilitation department.